New Medieval Literatures 19 - Knox, Philip 1988-; Robertson, Kellie 1968-; Scase, Wendy 1955-; Ashe, Laura ca. 20./21. Jh (D. S. Brewer, 2019)
An invigorating annual for those who are interested in medieval textual cultures and open to ways in which diverse post-modern methodologies may be applied to them. "Alcuin Blamires Review of English Studies"